Exploratory study of the interest of MR susceptibility-weighted imaging for the pre-operative assessment of pelvic endometriosis extent. Issue 118 (September 2019) - Pin, Louis; Monseau-Thiburce, Anne-Coline; Ziade-Coularis, Caroline; Benjamin, Alice; Menut, Fanny; Brun, Jean-Luc; Merlot, Benjamin; Chateil, Jean-François
Highlights: SWI detects hemorrhagic lesions of endometriosis with a better sensitivity than T1 weighted sequence. SWI provide valuable diagnosis findings and improve the diagnostic performance of MRI for pelvis endometriosis assessment. Quality of SWI in pelvic imaging is generally satisfactory. Abstract: Objective: To evaluate the performance of magnetic resonance imaging (MRI) with susceptibility-weighted imaging (SWI) in the assessment of endometriosis. Material and methods: This prospective study was performed during the diagnostic step or the pre-operative assessment of endometriosis, between June 2017 and April 2018. The MRI was conducted with a 3T MRI device; protocol included T2W, T1W, with and without fat-saturation sequences completed with a SWI sequence: T2-star weighted angiography (SWAN). The diagnostic performance values of MRI and inter-observer agreement were first evaluated with a conventional MR protocol and then with the complementary SWAN sequence by 2 readers. MRI results were correlated with surgical findings in patients who underwent laparoscopy. Results: 74 patients were included in the study, and among them 10 patients were treated by laparoscopy. 81% of the endometriosis lesions had signal losses on the SWAN sequence related to hemorrhagic character whereas only 52% of the lesions had T1-weighted hyperintense implants. Diagnostic performance of the MRI examination was improved by the use of the SWAN sequence compared to the conventional MR protocol (Se = 94% and Spe = 73% in complete protocol and Se = 88% and Spe = 69% in conventional protocol), especially for the involvement of torus uterinus, utero-sacral ligament and retro-cervical site. An excellent interobserver agreement (қ-value = 0, 94) was noted between the two readers. Conclusion: SWI can improve the diagnostic accuracy of MRI by allowing the detection of hemorrhagic character of endometriosis lesions.